INTEGRASI TEORI BELAJAR HUMANISTIK DALAM PRAKTIK PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Yenni Widyawati; Ahsanul Huda; Bambang Sumardjoko; Endang Fauziati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this study is to analyze the integration of humanistic learning theory in the practice of differentiated instruction in the 4th grade of SD Negeri 04 Karangsari, Jatiyoso, Karanganyar. This research employs a descriptive qualitative approach with a case study methodology. Data is collected through observation, interviews, and documentation techniques. In data analysis, the researcher will identify patterns and key findings from the interview, observation, and documentation data. Data validation is conducted by ensuring consistency among various data sources and avoiding research bias. The integration of humanistic learning theory in differentiated instruction at SD Negeri 04 Karangsari is observed when the teacher: 1) sets learning objectives; 2) maps the learning needs of students; 3) plans differentiation of content, process, product, and assessment; 4) groups students based on learning styles; 5) implements differentiation of content, process, and product; 6) conducts presentation and feedback sessions; 7) performs assessment and reflection.